2018
DOI: 10.1097/md.0000000000013209
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic features of a pair of Chinese identical twins with congenital insensitivity to pain and anhidrosis

Abstract: Rationale: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare autosomal recessive genetic disorder characterized by insensitivity to noxious stimulus and the absence of sweating. Fractures and joint destruction are common complications, but detailed studies on mineral and skeletal homeostasis are not available. Mental retardation is often reported, but detailed observations during childhood are lacking. Patient concerns: A pair of 46-month-old Chinese ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, a study done on two identical twins with CIPA reported multiple presentations of the twins with indifference to painful stimuli, yet abdominal pain was present, and recurrent episodes of fever of unknown etiology not responsive to antipyretics. [5] Although our patient's mental function was normal, many patients with CIPA develop mental retardation. [1] Innervated sweat glands were reported by one of the studies, but anhidrosis remains predominant.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…However, a study done on two identical twins with CIPA reported multiple presentations of the twins with indifference to painful stimuli, yet abdominal pain was present, and recurrent episodes of fever of unknown etiology not responsive to antipyretics. [5] Although our patient's mental function was normal, many patients with CIPA develop mental retardation. [1] Innervated sweat glands were reported by one of the studies, but anhidrosis remains predominant.…”
Section: Discussionmentioning
confidence: 62%
“…[1] Innervated sweat glands were reported by one of the studies, but anhidrosis remains predominant. [2,5] Regarding diagnosis, many studies reported no reaction to pain with having unexplained episodes of hyperpyrexia after birth accompanied by skin dryness. Some studies, including the current case, support the evidence of a delayed diagnosis of CIPA in childhood due to the occurrence of symptoms at a later age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations